2010
DOI: 10.1080/10550887.2010.489443
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Spiritual Orientation and Adaptation to Therapeutic Community Treatment

Abstract: The purpose of this study was to determine the extent to which spiritual orientation was associated with adaptation to therapeutic community treatment. Spiritual orientation was assessed by the Spirituality Self-Rating Scale, a measure consistent with the conceptualization of spirituality typically reflected in Alcoholics Anonymous members' views. Spiritual orientation was positively correlated with acceptance of therapeutic community principles and clinical progress. Further assessment of spirituality related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Lastly, because the study did not take into account other confounds that may have affected retention rates, the findings are limited in scope and warrant further investigation of specific factors that may influence treatment completion. For example, some studies have noted the importance of treatment readiness and motivation to change in retention outcomes; because level of spirituality has been positively associated with treatment readiness, 60, 61 findings from this study may have pointed to treatment readiness, not spirituality, as the stronger predictor of retention.…”
Section: Discussionmentioning
confidence: 59%
“…Lastly, because the study did not take into account other confounds that may have affected retention rates, the findings are limited in scope and warrant further investigation of specific factors that may influence treatment completion. For example, some studies have noted the importance of treatment readiness and motivation to change in retention outcomes; because level of spirituality has been positively associated with treatment readiness, 60, 61 findings from this study may have pointed to treatment readiness, not spirituality, as the stronger predictor of retention.…”
Section: Discussionmentioning
confidence: 59%
“…The majority of participants self-identified as Caucasian or White, ranging from 48.8% (Lucchetti, Koenig, Pinsky, Laranjeira, & Vallada, 2014) to 94.9% (Schaler, 1996(Schaler, , 1997. Nevertheless, seven studies (Dermatis, Guschwan, Galanter, & Bunt, 2004;Dermatis, James, Galanter, & Bunt, 2010;Flórez et al, 2015;Goldfarb, Galanter, McDowell, Lifshutz, & Dermatis, 1996;Lucchetti et al, 2014) reported that the majority of participants were not White. One study from Israel (Edelstein et al, 2020) reported participant identification as Jewish or Arab and another study from Kuwait (Bilal et al, 1990) reported participant identification as Arab or Kuwaiti.…”
Section: Section 32: Demographicsmentioning
confidence: 99%
“…Two studies, focused on understanding feedback from patients in an inpatient treatment centre which was founded by an Episcopalian pastor (Daytop), found that preference for and acceptance of spiritually-based therapeutic community treatment was related to a higher frequency of prayer/meditation and stronger self-identification as spiritual (Dermatis et al, 2004(Dermatis et al, , 2010. Higher spirituality, assessed by Adapted Intrinsic/Extrinsic Scale for Spiritual Orientation, also predicted more acceptance of, but not preference for, the therapeutic community principles (Dermatis et al, 2010). Results from the 2004 paper also showed that those who reported a higher belief in God more strongly preferred spiritually based interventions than those who did not, but no such difference was found in preference for the inclusion of 12step groups.…”
Section: Attitudes Of Those In Treatmentmentioning
confidence: 99%
“…Individuals who dropped out were significantly more likely to have a criminal history (consistent with the findings of Darke et al, 2012 (Cardoso, Chan, Berven, & Thomas, 2003), spirituality (Dermatis et al, 2010), and engagement and motivation (Klag, Creed, & O'Callaghan, 2010). Five studies included two time points with the gap between measured points varying in length from 4 -15 months post program completion, and were in pre and post format (Bankston et al, 2009;Dekel et al, 2004;López-Goñi et al, 2010;Messina et al, 2000;Zoccali et al, 2007).…”
Section: Retention and Dropout As Well As Mean Length Of Stay In Treamentioning
confidence: 49%
“…The aggregate mean age of participants was 30.52 years (range of means: 26.4 -37.2 years). Of those that reported age ranges, the minimum age was 18 years (Darke, Campbell, & Popple, 2012;Lopez-Goni et al, 2010;Miles, Wenzel, & Mandell, 2008), and the maximum age was 72 years (Dermatis, James, Galanter, & Bunt, 2010) Gender. The majority of study participants were male, and studies reported either the direct number of males or a percentage.…”
Section: Population Characteristicsmentioning
confidence: 99%